Adolescents and Christian Identity: Navigating Faith in the Digital Era - Leiria Meisyani; Lilis Orliani Clodia Ceti Simon; Astrid Maryam Yvonny Nainupu; Isaac Sean (Sekolah Tinggi Teologi Simpson Ungaran, 2026)
This study addresses the growing social relevance and scientific gaps in understanding how Christian youth navigate faith identity in an increasingly digital landscape. This study aims to analyse the dynamics of Christian youth faith formation in the digital ecosystem and to identify the theological dimensions that impact the development of authentic Christian identity. A systematic comparative literature review was conducted using peer-reviewed articles from 2010 to 2025, sourced from primary databases, and thematically analysed. The results reveal the emergence of hybrid faith communities that blend online and offline worship, the emergence of Moralistic Therapeutic Deism as a challenge to orthodox Christian identity, and the prospect of digital discipleship to enhance faith formation and mission outreach. The study emphasizes the important role of pneumatology in digital contexts while acknowledging limitations such as gaps in virtual manifestation and digital. This research recommends developing a digital literacy and theology curriculum and adopting a hybrid discipleship model to foster deeper spiritual formation amid digital challenges.